Basic writings of Bertrand Russell/ edited by Robert E.Egner and Lester E. Denonn - Russell, Bertrand; Egner, Robert E. (ed.); Denonn, Lester E. (ed.) (London, 2006)
This comprehensive anthology of Bertrand Russell's writings brings together his definitive essays from the period 1903 to 1959. It covers the most fertile and the most lasting work on every significant area he published in.
Keywords: "Russell, Bertrand-writings-philosophy"